German Political Parties: Correlation between Political Positioning and Social Composition of Parliamentary Groups - Maria Khorolskaya; Egor Katashevich (Современная Европа, 2025)
The article analyses the degree of correspondence between the political positioning of German parties and the social composition of their parliamentary groups in the 20th Bundestag. The study is based on German parties’ manifestos prepared for elec-tions in 2021, as well as the authors' dataset containing information about the socio-demographic characteristics of members of the Parliament (gender, age, origin), their religion, marital status, and whether they have children. The authors select key programmatic points that can be reflected in the social composition of the parlia-mentary groups and then rank the parties according to the radicalism of their state-ments. According to the hypothesis, the ordinal place of the party in these rankings associates with the structure of representation in the party. The study found depar-ture from traditional gender roles being combined with a greater representation of women. Supporting youth corresponds to a higher share of young deputies, and the ethnocultural diversity endorsement positively correlates with the percentage of migrants. Traditionalist agenda increases the likelihood a party member declares its own religiosity and the presence of children. At the same time, the more tolerant the party is toward Islam, the higher the percentage of Muslims is. In addition, it was found that in parties that build their identity around specialized issues, this identity is reflected in the social composition of its deputies. Thus, the emphasis on the pro-tection of Christian values by the CDU/CSU corresponds to a higher proportion of Christians. Among the Left, which pays special attention to the new federal lands, eastern Germans have higher representation.